สื่อออนไลน์กับการกำกับอารมณ์ทางการเมือง: กรณีศึกษาความขัดแย้งไทย–กัมพูชา - ถวิลไพร, เบญจวรรณ; ทิพยานุกูล, ชนัญชิดา; นาเมืองรักษ์, ยศธร (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 3 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 3 : กันยายน - ธันวาคม 2568, 2025)
This article aims to analyze the role of online media as a new public sphere that both mirrors and amplifies political emotions among citizens in the context of the Thailand–Cambodia conflict. The study focuses on historical, ethnic, and territorial sovereignty issues that often provoke emotional tension and polarization within digital communication spaces. Drawing upon the conceptual framework of political science and the Buddhist philosophical principle of the Kalama Sutta, the research investigates the process of regulating political emotions among online users. The analysis highlights the importance of mindfulness and critical reflection in filtering information before believing, sharing, or expressing emotions to foster rational and ethical engagement in political discourse. Findings indicate that online media have dual capacities: they can serve as platforms for participatory political learning and civic awareness, yet simultaneously act as arenas for hostility, hate speech, and digital bullying that erode mutual respect and international relations. Hence, regulating political emotions requires the integration of critical thinking and mindfulness to prevent misinformation, verbal aggression, and emotional manipulation. Applying the Kalama Sutta to online political communication encourages a culture of compassionate dialogue, reduces cross-border hostility, and enhances mutual understanding between Thai and Cambodian societies. Ultimately, this approach provides a philosophical and practical pathway toward peaceful coexistence within the democratic digital era.